2019
DOI: 10.3390/en12234424
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Effect on Water Transport through Nanotubes

Abstract: In this study, we used non-equilibrium molecular dynamics to study the transport of water through deformed (6,6) Carbon Nanotubes (CNTs) and Boron Nitride Nanotubes (BNNTs). The results were then compared with that of the perfect nanotubes. The main aim of this study was to get a better insight into the deformation effect on water transport through nanotubes rather than directly comparing the CNTs and BNNTs. As the diameters of both types of nanotubes differ from each other for the same chiral value, they are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Figure 4 shows the free energy of occupancy fluctuations of the molecules inside the nanopore for different patterns and angles. Detailed discussions regarding the free energy of occupancy fluctuations have been carried out in many previous studies [ 43 , 44 , 45 ]. The free energy of occupancy fluctuations can be calculated using the formula –ln[P(N)], where P(N) is the probability of finding the exact number of water molecules inside the nanopore at a given time.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4 shows the free energy of occupancy fluctuations of the molecules inside the nanopore for different patterns and angles. Detailed discussions regarding the free energy of occupancy fluctuations have been carried out in many previous studies [ 43 , 44 , 45 ]. The free energy of occupancy fluctuations can be calculated using the formula –ln[P(N)], where P(N) is the probability of finding the exact number of water molecules inside the nanopore at a given time.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies on the behavior of water molecules in the filtration system and near the membrane have demonstrated that the hydrogen bonds and the changes in this behavior are affected by an external electrical field. 51 As illustrated in Figure 12, the length of the hydrogen bond in the absence of an electric field is greater than the length of the bonds in the presence of an electric field; hence, the bonds are unstable, and they break at low electric fields. 52 Depending on the intensity of the electric field, it can cause electrolysis in an aqueous solution.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies on confined water bring illuminating results on the influence of hydrogen bonds and the changes in this behavior in the presence of external electrical charges [96]. It is interesting to mention that hydrogen bonds account for a large part of the interactions of the water molecules.…”
Section: Resultsmentioning
confidence: 99%